Muḍārabah and mushārakah as micro-equity finance: perception of Selangor's disadvantaged women entrepreneurs - Reazul Islam; Rubi Ahmad (ISRA International Journal of Islamic Finance, 2020)
Purpose: This study aims to gain the perception of Selangor's disadvantaged women on the Sharīʿah (Islamic law) rules on two micro-equity financing instruments, namely, muḍārabah (profit sharing) and mushārakah (profit-and-loss sharing) (M&M). Design/methodology/approach A survey was carried out in the rural area of Selangor district in Malaysia by administering a self-generated structured questionnaire. A total of 330 completed questionnaires were retrieved from the members of an Islamic microfinance institution (IsMFI), namely, Amanah Ikhtiar Malaysia (AIM). The data were analysed by using structural equation modelling. Findings The female borrowers of AIM perceive the Sharīʿah rules of M&M requiring high moral and ethical values and diligent repayment performance. They are aware of some other underlying provisions such as business liquidation, share transfer, information discloser and business termination. The overall findings of this study suggest that the perceived Sharīʿah rules are akin to those that are commonly used in general partnership businesses between Muslims. It also indicates that disadvantaged entrepreneurs would accept the rules that are easy to comprehend as well as favourable to their interests. It further suggests that respondents' experiences of microfinance and business operation do not have a significant influence on their perception of M&M instruments. Research limitations/implications This study was limited to Selangor. So, the perception of Muslim women surveyed may not represent the views of all women in Malaysia. However, it can offer a primary understanding of the said issue. Practical implications The findings of this study can help IsMIFs take initiatives to offer M&M as micro-equity finance to poor women entrepreneurs. Originality/value So far, limited studies have been carried out on M&M-based microfinancing. This paper offers new insights presenting disadvantaged women entrepreneurs' perception of these financing instruments.
Keywords: 330; Islamic microfinance; Muḍārabah; Mushārakah; Profit and loss sharing approach; Sharīʿah rules